(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Partially H[L‑d6]) and full (D[L‑d6]) deutero-substituted analogues of dimethyl-N-trichloroacetylamidophosphate (H[L]) as well as its sodium salts (Na[L]) and (Na[L‑d6]) have been synthesized. It was shown the possibility of their interconversion excepting the direct replacement of protons of the methyl groups on deuterons. The detailed comparative analysis of IR- spectra clearly allowed ascribing of the absorption bands corresponding to N-H and C-H valence and deformation vibrations in dimethyl-N-trichloroacetylamidophosphate molecule. The shape of the absorption band N-H in the region 3068 cm-1 (for N-D – 2262 cm-1) demonstrates the realization of imidic structure among three of theoretically possible tautomeric forms of H[L] in solid state. In the spectra of the sodium salts the absence of these bands indicates the existence of dimethyl-N-trichloroacetylamidophosphate in the anionic form. Isotopic substitution of methyl protons leads to a significant low-frequency shift of the bands of stretching and deformation vibrations: (nas+sC-H) 2958–2885 cm-1, (das+sC-H) 1460 cm-1 in the spectrum of H[L] and (nas+sC-D) 2274–2082 сm-1, (das+sC-D) 1335 сm-1 in the spectrum of D[L-d6] respectively. The low-frequency shifts (D » 60–100 сm‑1) of characteristic n(C=O) band were observed in the spectra of onic- salts and complexes due to delocalization of p-electron density in the OCNPO – chelate fragment under deprotonation or coordination. The same tendency reveals n(P=O) band (D » 38–128 сm‑1). The biggest low-frequency shift (128 cm-1) was fixed for this absorption band in the spectrum of SbPh4[L], that allowed the definition of the most preferable donor centre of dimethyl-N-trichloroacetylamidophosphate-anion [L]- - the oxygen atom of phosphoryl group.